A Works Council’s Response to Decent Work Deficits Facing Agricultural Employees in Zimbabwe - Moment Bhebhe; Prince Takaindisa (AESSRA, 2022)
This study examined the role and challenges faced by the works council in addressing decent work deficits within the agricultural industry in Zimbabwe. The pervasiveness of decent work deficits in organisations within the agricultural industry in the global economy, including in Zimbabwe, remains of major concern. To address this, the research took a qualitative case-study approach in a selected Agribusiness in Zimbabwe. The study involved 18 purposively selected participants, all who are members of the works council (management and workers’ committee), including experts from the human resource and industrial relations department in the organisation. Nine semi-structured interviews were conducted with the management participants and a focus group discussion was held with all the workers’ committee members. The major study findings revealed the presence of decent work deficits in the organisation. The works council members confirmed that the agrarian employees in the organisation face indecent work conditions characterised by insufficient wages, long hours of work, a lack of adequate personal protective clothing and insecurities attached to temporary employment. In addressing these deficits, the works council was found to be incapacitated due in part, to: failure to regularly hold meetings; constant use of threats by management against members of the workers’ committee; and inadequate knowledge and skills particularly on the part of the workers’ committee. It is recommended that the human resources and industrial relations department plays a more active role to ensure the effective functioning of the works council.